2015
DOI: 10.1007/s00775-015-1292-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the salicylaldehyde thiosemicarbazone scaffold for inhibition of influenza virus PA endonuclease

Abstract: The influenza virus PA endonuclease is an attractive target for the development of novel anti-influenza virus therapeutics, which are urgently needed because of the emergence of drug-resistant viral strains. Reported PA inhibitors are assumed to chelate the divalent metal ion(s) (Mg²⁺ or Mn²⁺) in the enzyme's catalytic site, which is located in the N-terminal part of PA (PA-Nter). In the present work, a series of salicylaldehyde thiosemicarbazone derivatives have been synthesized and evaluated for their abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 55 publications
3
33
0
Order By: Relevance
“…K) compounds, tetramic acid derivatives, polyphenolic catechins , trihydroxyphenyl ‐bearing compounds (Fig. D and K, compound 2 and compound 16), phenethylphenylphthalimide analogues derived from thalidomide, macrocyclic bisbibenzyls , fullerenes , hydroxyquinolinones , hydroxypyridinones , hydroxypyridazinones , hydroxypyrimidinones , β‐diketo acid (DKA) , and DKA‐bioisosteric compounds, bis‐dihydroxyindolecarboxamides , 2‐hydroxybenzamides , thiosemicarbazones , pyrimidinoles , pyridopiperazinediones (Fig. K, Endo‐1), and miscellaneous compounds bearing distinct pharmacophoric fragments .…”
Section: Strategies To Interfere With the Influenza Virus Polymerasementioning
confidence: 99%
“…K) compounds, tetramic acid derivatives, polyphenolic catechins , trihydroxyphenyl ‐bearing compounds (Fig. D and K, compound 2 and compound 16), phenethylphenylphthalimide analogues derived from thalidomide, macrocyclic bisbibenzyls , fullerenes , hydroxyquinolinones , hydroxypyridinones , hydroxypyridazinones , hydroxypyrimidinones , β‐diketo acid (DKA) , and DKA‐bioisosteric compounds, bis‐dihydroxyindolecarboxamides , 2‐hydroxybenzamides , thiosemicarbazones , pyrimidinoles , pyridopiperazinediones (Fig. K, Endo‐1), and miscellaneous compounds bearing distinct pharmacophoric fragments .…”
Section: Strategies To Interfere With the Influenza Virus Polymerasementioning
confidence: 99%
“…In particular, this approach led us to identify novel classes of influenza virus endonuclease inhibitors (i.e., salicyl thiosemicarbazones [25], and acyl hydrazones [26]), as well as original prototypes (i.e., pyrazole-carboxylic acids) of carbonic anhydrase inhibitors (CAIs) [27]. On this basis, we evaluated some representative compounds belonging to a general class of 4-(4-substituted-triazole)-benzenesulfonamides, specifically designed as CAIs, as putative HIV-1 RT-associated RNase H inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Interest in their antiviral properties dates back to the discovery of methysazone (Marboran ® ), which was used to treat smallpox prior to its global eradication [11]. More recent studies have reported activity against other poxviruses, herpes simplex virus or influenza virus [12]. Transformation of some 5-acetyl-2-phenylbenzimidazoles into the corresponding (thio)semicarbazone analogues yielded new agents with activity against HCV and the In the light of our previous findings, we deemed it interesting to explore new additional substitution patterns on the benzimidazole main core, with the aim of gaining a better understanding of the potential of this nucleus towards the development of novel series of antiviral agents.…”
Section: Introductionmentioning
confidence: 99%